KLAUSTROFOBIA I UCZUCIA Z NIĄ ZWIĄZANE W POLSKIM PRZEKŁADZIE POWIEŚCI DMITRIJA GŁUCHOWSKIEGO FUTU.RE - Darda-Gramatyka, Joanna (Przegląd Rusycystyczny, 2017)
The main character of the novel — and the author’s main subject of interest — is Jan, the Immortal 717. He suffers from claustrophobia and agoraphobia. The author discusses in details the idea of presupposition and its examples in the analysed text. Also, based on the specific examples from the text, she analyses many different feelings connected to Jan’s claustrophobia — such as fear, anxiety, panic — and their physiological symptoms Jan experiences.